INFLUENCE AND ROLE OF FAT ON THE SENSORY CHARACTERISTICS OF MEAT PRODUCTS - Belichovska, Daniela; Silovska Nikolova, Aleksandra; Petrov, Petar (University Ss. Cyril and Methodius in Skopje, 2024)
Fat plays a major role in the development of the sensory characteristics of meat and meat products. They affect the change of appearance, smell, aroma, texture, and especially the overall impression of meat products. Aroma is a joint impression of taste and smell that is felt during chewing. The specific aroma of some types of meat depends on the fat composition. Oxidation of pork and beef fat are important factors in creating the right smell and taste in these types of meat. In contrast, sheep fat creates a specific, strongly expressed aroma. The aroma of the product depends on the amount and type of fat (intermuscular, intramuscular, structural and adipose). Fat also affects the texture of meat products. Texture means: softness, juiciness, friability, fine bite sensation, toughness and elasticity, and it is a set of properties that can be evaluated sensory or instrumentally. Fats are important for the rheological and structural characteristics of meat products and for the formation of a stable emulsion. When shaping the texture of meat products, apart from the type and amount of added fat, the interaction of fat with other ingredients is of great importance. Reduc-ing the fat content below 15% contributes to the reduction of textural characteristics in the final meat product. The appearance and color of meat products are very important because they attract consumers the most and give the first visual impression of their quality. The attractiveness of the color depends on the muscle pigment − myoglobin, and its compounds. The fat content of meat affects its color. Marbled meat has a lighter color. A big reason for the reduction of typicality and color intensity of meat products is the replacement of animal fats with vegetable oils.
Keywords: fat; sensory characteristics; meat products